Optimization of sorbitol, glycerol, and propyleneglycol mixture in sunscreen gel of ethanolic extract of Curcuma mangga - Yuliani, Sri Hartati Hartati (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
The research about optimization of sorbytol, glycerol, and propyleneglycol mixture in sunscreen gel of ethanolic extract of Curcuma mangga has been done. The aims of this research was to discover the optimum mixture of sorbytol, glycerol and propyleneglycol that gave good physycal characteristic of the gel. First, made the ethanolic extract of Curcuma mangga as active ingredient. The SPF value of the ethanolic extract of Curcuma mangga was measured. Simplex lattice design was employed to create the optimum composition of sorbitol, glycerol and propyleneglycol in the sunscreen gel. Physical characteristic of the gel including spreadability, viscosity and the alteration of the gel viscosity was measured. The result showed that there were optimum composition between sorbytol, glycerol and propyleneglycol which gave good physical characteristics based on the shading area at the counterplot superimposed.Keywords: sorbitol, glycerol, propyleneglycol, Curcuma mangga, sunscreen gel